The secular good in denial: the The lesser evil and the politics of fright - Vahabzadeh, Peyman (The journal for cultural and religious theory, 2005)
A review of The Lesser Evil: Political Ethics in the Age of Terror, by Michael Ingatieff, (Princeton: Princeton University Press, 2004). xii + 212 pp.